Regulation of Wnt/β-catenin signaling by Marek’s disease virus in vitro and in vivo - Xu, Haiyin; Xu, Xihao; He, Huifeng; Shao, Hongxia; Yao, Yongxiu; Qin, Aijian; Qian, Kun (Frontiers in Microbiology, 2024)
Marek's disease virus (MDV) infection causes immunosuppression in the host, ultimately inducing tumor formation and causing significant economic losses to the poultry industry. While the abnormal activation of the Wnt/β-catenin signaling pathway is closely associated with the occurrence and development of tumors. However, the relationship between MDV and the Wnt/β-catenin pathway remains unclear. In this study, we found that the MDV RB1B strain, but not the MDV vaccine strain CVI988, activated the Wnt/β-catenin signaling pathway by increasing the phosphorylation level of GSK-3β in chicken embryo fibroblast (CEF). In vivo infection experiments in SPF chickens also confirmed that the RB1B strain activated the Wnt/β-catenin signaling pathway, while the CVI988 strain did not lead to its activation. Moreover, unlike the Meq protein encoded by the CVI988 strain, the Meq protein encoded by the RB1B strain specifically activated the Wnt/β-catenin signaling pathway in CEF cells. The findings from these studies extend our understanding of the regulation of Wnt/β-catenin signaling by MDV, which make a new contribution to understanding the virus-host interactions of MDV.